Pelatihan Membangun Personal Branding dan Kepercayaan Diri pada Siswa SMP Negeri 2 Mempawah Timur - Fitriandy, Rizki; Pebrianti, Wenny; Akbar, Muhammad Tareq; Almira , Andrea Marsha; Annisa, Sitti Nabilah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Personal branding is the process of shaping public perception of an individual's personality, abilities, or values to create a positive societal perception. It emphasizes the importance of managing one's self-image to compete in various aspects of life. This training program is designed for students of SMP Negeri 2 Mempawah Timur and includes training sessions and simulations. The goal of the training is to help students understand personal branding and develop self-confidence. In one of the simulation activities, students are required to present themselves in front of the class and explain how they would showcase their talents and potential to create their personal brand. The program aims to help middle school students adapt and implement self-confidence as a form of personal branding to support their personal, educational, and professional success. Through the training and simulations, students gain practical knowledge and skills that raise their awareness of the importance of self-development from an early age. Overall, this training plays a crucial role in preparing students to become excellent and qualified human resources, supporting them to compete in the educational and career realms, and contributing to achieving the vision for Indonesia Emas 2045.